Microenvironmental control of the ductular reaction: balancing repair and disease progression - Giovanni Sorrentino (Cell Death and Disease)
Abstract The ductular reaction (DR) is a dynamic adaptive cellular response within the liver, triggered by various hepatic insults and characterized by an expansion of dysmorphic biliary epithelial cells and liver progenitors. This complex response presents a dual role, playing a pivotal function in liver regeneration but, paradoxically, contributing to the progression of liver diseases, depending upon specific contextual factors and signaling pathways involved. This comprehensive review aims to offer a holistic perspective on the DR, focusing into its intricate cellular and molecular mechanisms, highlighting its pathological significance, and exploring its potential therapeutic implications. An up-to-date understanding of the DR in the context of different liver injuries is provided, analyzing its contributions to liver regeneration, inflammation, fibrosis, and ultimately carcinogenesis. Moreover, the review highlights the role of multiple microenvironmental factors, including the influence of extracellular matrix, tissue mechanics and the interplay with the intricate hepatic cell ecosystem in shaping the DR’s regulation. Finally, in vitro and in vivo experimental models of the DR will be discussed, providing insights into how researchers can study and manipulate this critical cellular response. By comprehensively addressing the multifaceted nature of the DR, this review contributes to a more profound understanding of its pathophysiological role in liver diseases, thus offering potential therapeutic avenues for hepatic disorders and improving patient outcomes.